Revisiting free school meal eligibility as a proxy for pupil socio‐economic deprivation. (12th January 2017) - Ilie, Sonia; Sutherland, Alex; Vignoles, Anna
Abstract : Whether someone has ever had free school meal (FSM) eligibility over a six‐year period is the measure of socio‐economic disadvantage currently used in the English school system. It is used to monitor the socio‐economic gap in achievement in the education system, to identify particular children at risk of low achievement and to direct funding to particular children and schools. In this paper we assess how well this measure predicts pupil attainment in secondary school in comparison to other measures of socio‐economic background known to influence pupil attainment, such as parental education or income. We ask whether the FSM measure is an adequate proxy for a pupil's socio‐economic disadvantage in an educational context. To do this we draw on the Longitudinal Study of Young People in England and matched administrative data. We find that the FSM eligibility measure correlates highly with other measures of socio‐economic disadvantage, however it does not identify all children living in what would be deemed deprived households. We then compare the extent to which the FSM eligibility measure predicts educational achievement relative to other measures of deprivation and find that its predictive power is only marginally lower than many richer survey measures. This provides some reassurance on its use in policy.